AN ANALYSIS OF THE MULTI – WORD EXPRESSIONS USED IN SPORTS NEWS STORIES: A CASE STUDY OF TEN SPORTS NEWS STORIES SELECTED FROM THE BANGKOK POST - Ingbarmee, Sutthinan; Kongkeaw, Prommintra (International Journal of Research -GRANTHAALAYAH, 2016)
The purposes of the study were to analyze the structure of the multi – word expressions used in sports news stories and to study types of the multi – word expressions used in sports news stories. The subjects of this study were10 sport news stories including five football news, three tennis news and two boxing news collected from the Bangkok Post from 27 September to 14 November 2014.The percentage was used for data analysis. The study found that the patterns of the multi-word expressions in those news stories could be detailed as follows. The structure used with the highest occurrence was Adjective + Noun, Asian Games; it accounts for 43.02% in ten news stories. The pattern mostly used in a second ranking was Noun + Noun, season-ending tournament; it accounts for 12.83 %. The structure ranked third in its use in the selected news stories was Noun +’s+ Noun, Spain’s Ferrer; it made up 18.11%. The structure came in fourth was Noun +of + Noun, Kuldep Singh of India; it represented 12.45 %. The structure came in fifth was Noun +Noun + Noun, World number three; it represented 7.17 %. Last, the structure Adjective + Noun+ Noun, Five Thai fighters, was the least used; it accounts for only 6.42 % in ten subjects.